2014
DOI: 10.1002/ejoc.201402207
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into the Palladium‐Catalyzed Domino Synthesis of 10,11‐Dihydro‐5H‐dibenzo[b,e][1,4]diazepines

Abstract: A palladium‐catalyzed domino approach to the synthesis of 10,11‐dihydro‐5H‐dibenzo[b,e][1,4]diazepines starting from o‐phenylenediamines and 2‐bromobenzyl bromides or tosylates has been developed. Mechanistic studies support the following domino sequence. Intermolecular mono‐N‐benzylation of the o‐phenylenediamine through oxidative palladium insertion, primarily at the benzylic position of the 2‐bromobenzyl bromide, is followed by intramolecular N′‐arylation. The intramolecular N′‐arylation is demonstrated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…As a practical alternative to dibenzodiazepinone reduction, Laha and co-workers developed a Pd/ L6 -catalyzed tandem process for the synthesis of 10,11-dihydro-dibenzodiazepines ( 136 ) ( Scheme 24 a). 120 Presumably, intermolecular Pd-catalyzed N-benzylation of 1,2-diaminoarenes with 2-bromobenzyl bromides occurs first, followed by intramolecular N-arylation to furnish the seven-membered-ring-containing heterocycles in 23–91% yield. 121 Additionally, Domínguez and co-workers prepared a series of (pyrazolo)dibenzodiazepines ( 140 ) in an effort to enhance the drug-like properties of the final compounds ( Scheme 24 b).…”
Section: Anilinesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a practical alternative to dibenzodiazepinone reduction, Laha and co-workers developed a Pd/ L6 -catalyzed tandem process for the synthesis of 10,11-dihydro-dibenzodiazepines ( 136 ) ( Scheme 24 a). 120 Presumably, intermolecular Pd-catalyzed N-benzylation of 1,2-diaminoarenes with 2-bromobenzyl bromides occurs first, followed by intramolecular N-arylation to furnish the seven-membered-ring-containing heterocycles in 23–91% yield. 121 Additionally, Domínguez and co-workers prepared a series of (pyrazolo)dibenzodiazepines ( 140 ) in an effort to enhance the drug-like properties of the final compounds ( Scheme 24 b).…”
Section: Anilinesmentioning
confidence: 99%
“…The Pd-catalyzed intramolecular coupling of anilines has also been used to prepare dibenzodiazepines, which are important pharmaceutical targets (Scheme ). As a practical alternative to dibenzodiazepinone reduction, Laha and co-workers developed a Pd/ L6 -catalyzed tandem process for the synthesis of 10,11-dihydro-dibenzodiazepines ( 136 ) (Scheme a) . Presumably, intermolecular Pd-catalyzed N-benzylation of 1,2-diaminoarenes with 2-bromobenzyl bromides occurs first, followed by intramolecular N-arylation to furnish the seven-membered-ring-containing heterocycles in 23–91% yield .…”
Section: Anilinesmentioning
confidence: 99%
“…[32] It should also be noted that we have had little success -despite numerous studies and efforts -to successfully achieve the same results using the structurally analogous, o-haloarylketimines. [34] In 2014, Laha et al [35] reported a palladium-catalyzed domino approach for the synthesis of a dihydro-DBDA class (10,11dihydro-5H-dibenzo[b,e][1,4]diazepines) starting from o-phenylenediamines and 2-bromobenzyl bromides or tosylates (Scheme 7). [34] In 2014, Laha et al [35] reported a palladium-catalyzed domino approach for the synthesis of a dihydro-DBDA class (10,11dihydro-5H-dibenzo[b,e][1,4]diazepines) starting from o-phenylenediamines and 2-bromobenzyl bromides or tosylates (Scheme 7).…”
Section: 4-dibenzodiazepinesmentioning
confidence: 99%
“…Very recently, we have developed an expedient domino synthesis of 10,11-dihydro-5H-dibenzo[b,e] [1,4]diazepines that are otherwise difficult to obtain by literature methods. 4 The methodology provided a workable access to various substituted 10,11-dihydro-5H-dibenzo[b,e] [1,4]diazepines for a general structure−activity relationship study.…”
mentioning
confidence: 99%
“…Very recently, we have developed an expedient domino synthesis of 10,11-dihydro-5H-dibenzo[b,e] [1,4]diazepines that are otherwise difficult to obtain by literature methods. 4 The methodology provided a workable access to various substituted 10,11-dihydro-5H-dibenzo[b,e] [1,4]diazepines for a general structure−activity relationship study. In this context, we had an opportunity to demonstrate the proof-of-concept on 10,11-dihydro-5H-dibenzo[b,e] [1,4]diazepines containing a cyclic secondary benzylamine moiety.…”
mentioning
confidence: 99%